A novel strain sensor based on the campaniform sensillum of insects. - Skordos, Alexandros A.; Chan, P. H.; Vincent, Julian F. V.; Jeronimidis, G. (Royal Society, 2002)
The functional design of the campaniform sensillum was modelled as a hole in a plate using two– and three–dimensional finite–element modelling. Different shapes of opening in a fibrous composite plate amplify differently the global strains imposed on the plate, and different configurations of reinforcement also have an effect. In this paper, the main objective is to study the strain and displacement fields associated with circular or elliptical openings in laminated plates in order to investigate their potential for integrated strain sensors. Since we are therefore primarily interested with the detection of displacement, the detailed stress concentration levels associated with these openings are not of primary concern. However, strain energy density levels associated with different hole and fibre configurations have been used to assess the relative likely strength reduction effect of the openings. To compare the relative strain amplification effect of drilled and formed holes of the same size in loaded plates, we have used the relative change in length of diameters (circular) or semi–axes (elliptical) in directions parallel and normal to the load. Various techniques which could sense this deformation were investigated, in particular, the coupling mechanism of a campaniform sensillum of Calliphora vicina. This mechanism was resolved into discrete components: a cap surrounded by a collar, a joint membrane and an annulus–shaped socket septum with a spongy compliant zone. The coupling mechanism is a mechanical linkage which transforms the stimulus into two deformations in different directions: monoaxial transverse compression of the dendritic tip and vertical displacement of the cap. The mechanism is insensitive to change of the material properties of the socket septum, the cuticular cap and the spongy cuticle. The joint membrane may serve as a gap filler. The material properties of the collar have a substantial influence on the coupling mechanism's output. A 30% change of stiffness of the collar causes 45% change in the output of the coupling mechanism. The collar may be able to tune the sensitivity of the sensillum by changing its elastic properties.
Keywords: hole; stress concentration; campaniform sensillum; fibrous composite; mechanical sensing; biomimetics